Hermeneutic Considerations in Translating Philosophical and Religious Texts - Ayatollahy, Hamidreza (Iranian Journal of Translation Studies, 2006)
As Iranians became more interested in and attracted to understanding the philosophical and religious schools of thought after the revolution, many translations of important Western books and articles appeared on those schools. But these translations and their contents have encountered serious challenges. If those challenges are neglected we will experience a kind of misunderstanding of Western thoughts as well as some irrelevant cultural influences of those thoughts. In this paper, I will present some vulnerabilities of translation of philosophical and religious texts; and focus on the necessity of seriously considering the hermeneutic foundations of these translations so that it will be possible to have suitable interpretation of the translated ideas.